Pengaruh Model Pembelajaran Two Stay Two Stray Dipadu Picture And Picture Terhadap Hasil Belajar Ips Siswa Kelas IV SDN Gugus 06 Cakranegara Tahun Pelajaran 2020/2021 - Widyastuti, Ni Nyoman Santi; Saputra, Heri Hadi; Oktaviyanti, Itsna (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to determine the effect of the two stay two stray learning model combined with picture and picture on social studies learning outcomes for fourth grade students of SDN Gugus 06 Cakranegara in the 2020/2021 academic year. This research is a quantitative research with a quasi-experimental nonequivalent control group design . The population in this study were all fourth grade students at SDN Gugus 06 Cakranegara in the 2020/2021 academic year, while the samples in this study were fourth grade students at SDN 35 Cakranegara as the experimental class and fourth grade students at SDN 14 Cakranegara as the control class with purposive sampling. The results of data analysis obtained the value of sig. 2 tailed is 0.007 which the value is less than 0.05, then based on the research hypothesis, if the value of sig. 2 tailed <0:05 t-table then H0 is rejected and Ha diterime. This shows that there is an effect of the two stay two stray learning model combined with picture and picture on the social studies learning outcomes of fourth graders at SDN Gugus 06 Cakranegara in the 2020/2021 school year. The conclusion of this study is that the two stay two stray learning model combined with picture and picture has a change in students' cognitive learning outcomes seen from the learning process in the classroom and the two stay two stray learning model combined with picture and picture has a significant effect on student learning outcomes based on the hypothesis test obtained sig. 2 tailed is 0.007 < 0.05. The influence of the two stay two stray learning model combined with picture and picture on social studies learning outcomes is 0.22, which is included in the large category.